2014
DOI: 10.1523/jneurosci.0832-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Dosage-Dependent Effect of Dopamine D2 Receptor Activation on Motor Cortex Plasticity in Humans

Abstract: The neuromodulator dopamine plays an important role in synaptic plasticity. The effects depend on receptor subtypes, affinity, concentration level, and the kind of neuroplasticity induced. In animal experiments, dopamine D 2 -like receptor stimulation revealed partially antagonistic effects on plasticity, which might be explained by dosage dependency. In humans, D 2 receptor block abolishes plasticity, and the D 2 /D 3 , but predominantly D 3 , receptor agonist ropinirol has a dosage-dependent nonlinear affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 43 publications
(6 reference statements)
8
57
0
Order By: Relevance
“…Contextually, Met carriers in our study demonstrating significantly lesser percentage reduction of auditory hallucinations is in tune with these previous observations (Plewnia et al, 2013). Dopaminergic basis has been postulated to underlie the plasticity modulation effects of tDCS (Fresnoza et al, 2014). Thus, the observed finding might be linked to the differential effects of COMT Val158Met polymorphism on cortical dopamine levels.…”
Section: Discussionsupporting
confidence: 91%
“…Contextually, Met carriers in our study demonstrating significantly lesser percentage reduction of auditory hallucinations is in tune with these previous observations (Plewnia et al, 2013). Dopaminergic basis has been postulated to underlie the plasticity modulation effects of tDCS (Fresnoza et al, 2014). Thus, the observed finding might be linked to the differential effects of COMT Val158Met polymorphism on cortical dopamine levels.…”
Section: Discussionsupporting
confidence: 91%
“…While neurophysiological studies in healthy individuals have established a short-term interaction between tDCS and pharmacological agents [71], [72], [8], [73], there is minimal information on the interaction between tDCS and pharmacologic intervention in the treatment of mood disorders. The available evidence suggest potential synergistic effects at least in the treatment of depression [74],[75],[69].…”
Section: Tdcs Special Consideration For Safety In Mood Disordersmentioning
confidence: 99%
“…inverted-U-shaped dose-response profiles of postsynaptic dopamine effects in the prefrontal cortex has been described for working memory [11,14,29,30]. Similar dosedependent effects of D2 receptors on neuronal plasticity have been described in human motor cortex [31,32] while D2 was antagonized for L-Dopa stimulation of D1 [33]. Skinbjerg et al [34] reported a decrease in in vivo radio-ligand binding to the dopamine 2 receptor during PET studies after amphetamine induced increased extracellular dopamine for several hours.…”
Section: Discussionmentioning
confidence: 72%